Potensi Pemanfaatan Sabut Pinang (Arecha cathecu L.) Kecamatan Lengayang sebagai Sumber Karbon untuk Bahan Baku Material Maju - Nadia Nadia; Umar Kalmar Nizar (Departemen Kimia FMIPA UNP, 2023)
Carbon material is one example of the development of advanced materials. Carbon is the result of the decomposition of an organic compound through an incomplete carbonization process. Carbon can be utilized from organic waste materials such as areca fiber. The composition of areca nut is 32.98% hemicellulose, 7.20% lignin, 53.20% cellulose, and 4.81% other components remaining in areca nut. Cellulose in betel nut can be used as a source of advanced materials. The method used for the manufacture of areca fiber carbon is calcination at a temperature variation of 250oC, 300oC and 350oC. Proximate analysis of carbon was carried out by testing the ash content, vapor content and bound carbon content. In this research, the standard used is SNI 06-3730-1995. The results of the analysis show that the ash content increases with the increase in the calcination temperature, while the vapor content decreases with the increase in the calcination temperature. The carbon content obtained decreases with increasing calcination temperature. The optimum condition of areca fiber carbon that is close to SNI 06-3730-1995 is obtained on carbon with a calcination temperature of 250oC, with an ash content of 8.85%, a vapor content of 3.12% and a bound carbon content of 88.03%.